The Use of Social Media in Pandemic Times - Tedjo, Tony; Febrian, Cindy Clarrisa Gabriela; Nidin, Solihin bin; Handi, Tirza Raidishya Fairha Ayumi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research was conducted in which during the COVID -19 pandemic, there were a lot of people, including teenagers, early childhood, even parents, could misuse social media in their personal lives. Moreover, social media is a means where we can easily communicate with each other from a distance or a short distance. Moreover, from the various definitions of social media, it is also emphasized that social media is indeed very influential for us users and plays a perfect role. It also discusses how the right way to use social media during this pandemic is what we have to do during a pandemic like this.